Quantitative characterization of CO based on indentation experiment 2 Water-rock reaction erosion method
Through nano-indentation experiments, the mineral reaction area is divided on the surface of rock samples, and the mechanical parameters under erosion are calculated, which solves the problem that the existing technology cannot calculate the depth of rock erosion, and achieves the accuracy of safety assessment of CO2 geological sealing projects.
Patent Information
- Application Number
- CN202410350080.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-26
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-03-26
AI Technical Summary
The existing technology cannot effectively calculate the erosion load and erosion depth of local mineral reaction areas under rock erosion, resulting in the inability to quantitatively judge the erosion degree of rocks in the target reservoir, affecting the safety of CO2 geological storage projects.
Using an indentation experiment method, the mineral reaction area is divided on the surface of rock samples through nano-indentation test, and multi-load cycle loading is performed to calculate the elastic modulus, hardness and rebound stiffness before and after erosion, and determine the erosion load and maximum indentation. Depth, achieving quantitative characterization of erosion degree.
Accurately characterize the erosion degree of water-gas-rock erosion reactions under the nano-micrometer scale, and can directly calculate the erosion depth of the rock surface, improve the accuracy of judging the erosion degree of rock in the target reservoir, and ensure the safety of CO2 geological storage projects .
Smart Images

Figure CN118067552B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rock surface erosion research, and specifically relates to a method for quantitatively characterizing the erosion of CO2 water-rock reaction based on an indentation experiment. Background Art
[0002] CO 2 Gas injection into the target reservoir will cause water-CO 2 The chemical erosion reaction of the rock has a great impact on the mechanical properties of the reservoir rock. Therefore, how to judge the erosion degree of the target reservoir rock is very important for timely measuring the CO 2 The safety of geological storage projects is of great significance. Nanoindentation testing is a common means of obtaining the microscopic mechanical properties of rocks. However, at present, conventional triaxial and true triaxial mechanical testing equipment are usually used in laboratories to conduct mechanical experiments on rocks after erosion. The overall mechanical parameters such as hardness, modulus, and rebound stiffness can only be simply tested by pressing down on the entire rock sample. However, there is a lack of calculation methods for the erosion load and erosion depth of the local mineral reaction area under rock erosion, which makes it impossible to judge the erosion degree of the target reservoir rock. Summary of the invention
[0003] The present invention aims to provide a method for quantitatively characterizing CO based on indentation experiment. 2 The method for measuring the erosion degree of water-rock reaction is simple and convenient to test and operate, and the erosion depth is accurately calculated. It solves the problem that the erosion degree of the target reservoir rock cannot be quantitatively determined due to the lack of calculation methods for the erosion load and erosion depth of the local mineral reaction area under rock erosion.
[0004] To this end, the technical solution adopted by the present invention is: a method for quantitatively characterizing CO based on indentation experiment 2 The method for determining the erosivity of water-rock reaction comprises the following steps:
[0005] Step S1: Grind and polish the rock sample until the surface roughness meets the test requirements of the nanoindentation experiment, and then pretreat the rock sample according to the CO 2 The difficulty of water-rock reaction divides the mineral reaction areas on the surface of rock samples;
[0006] Step S2: Select a first test area in the mineral reaction area on the surface of the rock sample, and perform a matrix-type nanoindentation test with multiple load cycles, and calculate the elastic modulus E under each load before the erosion of the area based on the load-displacement curve obtained by the nanoindentation test. n , Hardness H n , rebound stiffness S n ;
[0007] Step S3, treating the rock sample through a high temperature and high pressure immersion test device to quickly simulate the erosion phenomenon on the rock surface, and then naturally air-drying;
[0008] Step S4: Select a second test area in the same mineral reaction area on the surface of the rock sample, and perform a matrix-type nanoindentation test with multiple load cycles, and the first test area and the second test area do not affect each other, and calculate the elastic modulus E under each load after the erosion of the area based on the load-displacement curve obtained by the nanoindentation test. n ', Hardness H n ', Rebound stiffness S n ';
[0009] Step S5: The elastic modulus E obtained by two nanoindentation tests before and after the erosion n With E n ', Hardness H n With H n ', Rebound stiffness S n With S n 'Conduct comparative analysis, when load F n The rebound stiffness S n ' and the rebound stiffness S of the first test area under the initial load 1 When closest, load F n is the erosion load in the main mineral reaction area; when the hardness H n ' or elastic modulus E n 'The corresponding load F when reaching the maximum n is the erosion load; finally, the maximum indentation depth is calculated by the erosion load as the erosion depth.
[0010] As a preferred embodiment of the above scheme, in step S1, the rock sample is a block rock sample, and the rock surface is finely polished step by step by sandpaper of various mesh sizes, and finally the rock surface is polished by an argon ion polishing device until the rock surface roughness meets the requirements of the nanoindentation experiment. Compared with the existing conventional uniaxial and conventional triaxial mechanical testing equipment, the rock sample size required is a cylinder with a diameter of 50 cm and a height of 100 cm, and the rock sample size required by the existing true triaxial mechanical testing equipment is a cube of 100 cm×100 cm×100 cm. The rock sample size adopted in this scheme is a block rock sample of 1 cm~2 cm×1 cm~2 cm×0.5 cm~2 cm, which is light and convenient for experimental operation.
[0011] CO of regular size rocks 2It takes a long time for water-rock reaction to affect rock mechanics specimens, and the native cracks in conventional-sized rock specimens will affect the calculation of erosion depth. On the other hand, since water-rock reaction mainly occurs at the microscopic level, the current conventional mechanical testing equipment can only test the mechanical properties of the macroscopic whole, while nanoindentation experiments can achieve quantitative characterization of erosion depth at the micro-nano scale.
[0012] More preferably, in step S1, the rock sample pretreatment process is to use a SEM / EDS electron microscope to determine the strength of the heterogeneity of the rock sample.
[0013] The heterogeneity of the rock sample can be judged by performing random SEM observations on the surface of the rock sample and scanning the components of the observation area using EDS. If the mineral components of the multiple observation areas are complex and numerous, the rock heterogeneity is considered to be strong; if the mineral components of the multiple observation areas are relatively simple, the rock heterogeneity is considered to be weak; and for rocks with strong heterogeneity, it is necessary to divide the rock sample surface into areas prone to CO 2 Different mineral reaction areas of water-rock reaction are considered, and it is believed that the mechanical properties in this area are mainly affected by the minerals in this area; while for heterogeneous weak rocks, it is believed that the mechanical properties of the rock sample are mainly affected by a single mineral and the mineral can produce CO 2 Water-rock reaction, therefore, only the main representative mineral reaction areas need to be divided, and the design idea is reasonable.
[0014] Further preferably, in the step S2, the nanoindentation experiment setting conditions are 50mN, 100mN, 160mN, 210mN, 270mN, 320mN, 370mN, 430mN, 480mN step-by-step loads and 3×3 matrix point arrangement, and the loading scheme of non-equal multiple load cycle loading can obtain the changes of the measured mechanical parameters of the sample with the increase of indentation depth, so as to determine the corrosion of the sample at different indentation depths, and the matrix point arrangement can realize the statistical analysis of the hardness, elastic modulus and rebound stiffness measured by the indentation experiment, so as to more reasonably represent the mechanical parameters of the area at different indentation depths;
[0015] In step S2, the matrix point arrangement of the nanoindentation test covers the first test area, and there is no interference between the indentation points. In step S4, the matrix point arrangement of the nanoindentation test covers the second test area, and there is no interference between the indentation points, so as to ensure the independence of the indentation test results in the first test area and the second test area.
[0016] More preferably, in step S5, the hardness H n With H n ', elastic modulus E n With E n ', Rebound stiffness Sn With S n ' are the average values of hardness, elastic modulus and rebound stiffness calculated at each indentation point in the matrix distribution in the corresponding first test area or second test area under the same load, and the calculation is reasonable.
[0017] More preferably, in step S5, each indentation point in the matrix in the second test area is placed under the erosion load F n The maximum indentation depth h max The average value is calculated to obtain the erosion depth h n , the calculation idea is reasonable and the erosion depth data is calculated accurately.
[0018] Beneficial effects of the present invention:
[0019] (1) Compared with the current lack of methods for calculating the erosion load and erosion depth of local mineral reaction areas under rock erosion, this scheme can quantitatively characterize the degree of erosion caused by the water-gas-rock erosion reaction on the rock surface at the nano-micrometer scale. Through the mechanical properties such as rebound stiffness, hardness and elastic modulus obtained by nanoindentation testing, the erosion depth of the rock surface can be directly calculated quantitatively. The concept is novel and the design is ingenious.
[0020] (2) Conventional uniaxial, conventional triaxial, and true triaxial tests can only measure the overall mechanical properties of rocks, while nanoindentation tests can use a matrix-based multi-load cyclic loading test scheme to achieve step-by-step measurement of the mechanical properties of the rock surface, thereby achieving the purpose of calculating the erosion depth of the rock surface. Due to the heterogeneity of the rock surface, there are single or multiple mineral reaction areas on the surface of the rock sample, so it is necessary to divide the mineral reaction areas and conduct precise tests on them. The data is highly accurate and meets actual needs. It can accurately determine the erosion degree of the target reservoir rock, thereby timely measuring the CO 2 Safety of geological storage projects.
[0021] (3) Elastic modulus E obtained from two nanoindentation tests before and after erosion n With E n ', Hardness H n With H n ', Rebound stiffness S n With S n 'Compare the results and analyze them, so as to obtain the erosion load of the mineral reaction area on the surface of the rock sample, and calculate the maximum indentation depth through the erosion load. The idea is novel, and through a variety of data comparison and analysis, they are mutually verified. Due to the elastic modulus E n , Hardness H n As the load increases, it gradually decreases, while the elastic modulus E n ', Hardness H n'With the increase of load, it first increases and then decreases. When the hardness or elastic modulus increases with the increase of load, the nanoindentation head still acts on the eroded layer area. When the hardness or elastic modulus reaches the maximum, it begins to act on the uneroded layer area. Therefore, when the hardness H n ' or elastic modulus E n 'The corresponding load F when reaching the maximum n For erosion load, cleverly combined with elastic modulus E n , Hardness H n The correlation changes with the load are novel.
[0022] (4) Due to the increase in the surface roughness of the rock sample after erosion, the calculation of the indentation contact area is unstable during the indentation test, resulting in fluctuations in the calculated hardness and elastic modulus. The rebound stiffness is determined by the slope of the initial stage of the rebound curve and is not affected by the indentation contact area. Therefore, using the rebound stiffness as a judgment criterion can avoid the interference of the surface roughness caused by erosion on the indentation test results. n , rebound stiffness S n 'To find the erosion load, only when the rebound stiffness S n 'Closest to the rebound stiffness S 1 When , it indicates that the nanoindentation head will act or has acted on the un-eroded layer area, so the erosion load data obtained is more accurate, thereby ensuring the accuracy of the erosion depth data. It can also be used to verify the erosion load data compared by hardness and rebound stiffness. The idea is ingenious.
[0023] In summary, it has the advantages of quantitative calculation of erosion depth, novel concept, meeting actual needs, accurate erosion load depth data, and accurate judgment of rock erosion degree. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a flow chart of the present invention.
[0025] Figure 2 Schematic diagram of the division of mineral reaction zones of rock samples (Figure a is a schematic diagram of the division of zones with strong heterogeneity of rock samples; Figure b is a schematic diagram of the division of zones with weak heterogeneity of rock samples).
[0026] Figure 3 Schematic diagram of the matrix layout of nanoindentation testing.
[0027] Figure 4 Schematic diagram of multiple load cycles for nanoindentation testing.
[0028] Figure 5 This is a demonstration graph of the multi-load cycle nanoindentation test curve.
[0029] Figure 6Demonstration analysis diagram of load-displacement curve of nanoindentation test.
[0030] Figure 7 This is a demonstration diagram of the change in hardness with load before and after erosion.
[0031] Figure 8 This is a demonstration diagram of the change of elastic modulus with load before and after erosion.
[0032] Fig. 9 This is a demonstration diagram of the change in rebound stiffness with load before and after erosion.
[0033] Fig.10 This is the SEM / EDS electron microscope observation image of white coal rock sample.
[0034] Fig.11 This is the nanoindentation test curve of the white coal rock sample before erosion.
[0035] Fig.12 This is the nanoindentation test curve of the white coal rock sample after erosion.
[0036] Fig.13 This is a comparison chart of the hardness under different loads obtained before and after erosion of white coal rock samples.
[0037] Fig.14 This is a comparison chart of the elastic modulus under different loads obtained before and after erosion of white coal rock samples.
[0038] Fig.15 This is a comparison chart of the stiffness under different loads obtained before and after erosion of white coal rock samples. DETAILED DESCRIPTION
[0039] The present invention will be further described below by way of embodiments and in conjunction with the accompanying drawings:
[0040] Combination Figure 1 — Fig.15 As shown in the figure, a quantitative characterization of CO based on indentation experiment 2 The method of water-rock reaction erosion degree is implemented as follows:
[0041] Step S1: Grind and polish the rock sample until the surface roughness meets the test requirements of the nanoindentation experiment, and then pretreat the rock sample according to the CO 2 The difficulty of water-rock reaction divides the mineral reaction areas on the surface of rock samples.
[0042] In step S1, the rock sample is a block rock sample, and the rock surface is finely polished step by step using sandpaper of various mesh sizes, and finally the rock surface is polished using an argon ion polishing device until the rock surface roughness meets the requirements of the nanoindentation experiment.
[0043] In step S1, the rock sample pretreatment process is to use SEM / EDS electron microscope to determine the strength of the heterogeneity of the rock sample.
[0044] Figure 2 A schematic diagram of the mineral reaction zone division of rock samples is shown.
[0045] like Figure 2 As shown in a, the mineral components in the observation area are complex and diverse, and the rock is highly heterogeneous, dividing it into a variety of mineral reaction areas.
[0046] like Figure 2 As shown in b, the mineral composition of the observation area is relatively simple, the rock heterogeneity is weak, and the main representative mineral reaction area is divided.
[0047] Step S2: Select a first test area in the mineral reaction area on the surface of the rock sample, and perform a matrix-type nanoindentation test with multiple load cycles, and calculate the elastic modulus E under each load before the erosion of the area based on the load-displacement curve obtained by the nanoindentation test. n , Hardness H n , rebound stiffness S n .
[0048] In step S2, the matrix layout of the nanoindentation test covers the first test area, and there is no interference between the indentation points.
[0049] Figure 5 A demonstration graph of multi-load cycle nanoindentation test curves is shown.
[0050] During the nanoindentation test, the load-displacement curve of each nanoindentation test is recorded; Figure 6 An exemplary analysis diagram of the load-displacement curve of the nanoindentation test is shown.
[0051] According to the load-displacement curve obtained by the nanoindentation test, the elastic modulus E of the rock sample under each load at the indentation point can be calculated by the following formula: mn , Hardness H mn , rebound stiffness S mn .
[0052] Therefore, the elastic modulus E representing the mineral reaction zone before erosion under various loads can be obtained by the following formula n , hardness H n , rebound stiffness S n .
[0053] mIndentation point F n Elastic modulus E of rock sample under load mn The calculation formula is as follows:
[0054]
[0055] In the formula, E i is the elastic modulus of the nanoindenter tip, E mn The rock sample is at point m F n Modulus of elasticity under load, v i and v are the Poisson’s ratios of the nanoindenter tip and the rock being tested, respectively; E is usually taken as i =1140GPa,v i =0.07, the rock Poisson's ratio is determined by the mechanical test of the sample to be tested, E r is the reduced modulus of the sample under this condition.
[0056] mIndentation point F n Hardness of rock sample under load H mn The calculation formula is as follows:
[0057]
[0058] Where F max is the indentation point F n Maximum load of nanoindentation test curve under load, A c is the contact area between the nanoindenter tip and the shale surface.
[0059] mIndentation point F n Rebound stiffness S of rock sample under load mn The calculation formula is as follows:
[0060]
[0061] That is S mn is the initial slope of the unloading curve in the nanoindentation experiment under this condition.
[0062] E r is the reduced modulus of the sample to be tested under this condition, and the calculation formula is as follows:
[0063]
[0064] Where β is the geometric correction factor, which depends on the geometry of the indenter, S mn is the rebound stiffness.
[0065] A c is the contact area between the nanoindenter tip and the shale surface, and the calculation formula is as follows:
[0066] A c =24.5h c 2
[0067] h c =h max-ε(h max -h r )
[0068] Where h c is the contact depth, h max is the peak depth; h r is the tangential depth of the unloading curve; ε is a constant related to the geometry of the pressure head.
[0069] The elastic modulus E of each indentation point under each load calculated using the above formula mn , Hardness H mn , rebound stiffness S mn The average value is calculated to obtain the elastic modulus E of the main minerals in the area under various loads. n , Hardness H n , rebound stiffness S n , the calculation formula is as follows:
[0070]
[0071]
[0072]
[0073] Step S3: The rock sample is treated by a high temperature and high pressure immersion test device to quickly simulate the erosion phenomenon on the rock surface, and then naturally air-dried.
[0074] Step S4: Select a second test area in the same mineral reaction area on the surface of the rock sample, and perform a matrix-type nanoindentation test with multiple load cycles under the same experimental conditions, and the first test area and the second test area do not affect each other, and calculate the elastic modulus E under each load after erosion of the area based on the load-displacement curve obtained by the nanoindentation test. n ', Hardness H n ', Rebound stiffness S n '.
[0075] In step S4, the matrix layout of the nanoindentation test covers the second test area, and there is no interference between the indentation points.
[0076] Elastic modulus E n ', Hardness H n ', Rebound stiffness S n ' can be calculated by the formula in step S2.
[0077] Step S5: The elastic modulus E obtained by two nanoindentation tests before and after the erosion n With E n ', Hardness H n With H n', Rebound stiffness S n With S n 'Conduct comparative analysis, when load F n The rebound stiffness S n ' and the rebound stiffness S of the first test area under the initial load 1 When closest, load F n is the erosion load in the mineral reaction area; when the hardness H n ' or elastic modulus E n 'The corresponding load F when reaching the maximum n is the erosion load; finally, the maximum indentation depth is calculated by the erosion load as the erosion depth.
[0078] In step S5, the elastic modulus E n With E n ', Hardness H n With H n ', Rebound stiffness S n With S n ' are respectively the average values of elastic modulus, hardness and rebound stiffness calculated at each indentation point in the matrix distribution in the first test area or the second test area under the same load.
[0079] Figure 7 — Fig. 9 Demonstration graphs showing changes in hardness, elastic modulus, and rebound stiffness with load before and after erosion are shown.
[0080] In step S5, each indentation point in the matrix of the second test area is placed under the erosion load F n The maximum indentation depth h max The average value is calculated to obtain the erosion depth h n , the formula is as follows:
[0081]
[0082] In the formula, h max For point m at F n Maximum indentation depth under load.
[0083] Example
[0084] The coal cores taken from the Baijiao Coal Mine were cut into 1cm×1cm×1cm cubic rock specimens. One surface of the specimen was polished in turn using 600-mesh, 1200-mesh, 2000-mesh, 5000-mesh, and 7000-mesh sandpapers. Then, the surface was finely polished using argon ion polishing until the surface roughness of the sample reached the nanoindentation test standard.
[0085] The strength of the rock sample heterogeneity is determined by performing multiple random SEM observations on the surface of the rock sample and using EDS to scan the components of the observation area. It is thus determined that the coal sample is a rock sample with strong heterogeneity. A point-like mineral reaction area mainly composed of carbonates is obtained, and it is believed that the mechanical properties in this area are mainly determined by the mechanical properties of carbonates.
[0086] Fig.10 Shown is the SEM / EDS electron microscope observation image of white coal rock sample.
[0087] In the divided carbonate point mineral reaction area, the first test area is selected using the optical or electron microscope of the nanoindentation tester, and a multi-load cycle loading nanoindentation experiment is performed in the first test area. The nanoindentation experiment setting conditions are 50mN, 100mN, 160mN, 210mN, 270mN, 320mN, 370mN, 430mN, 480mN step-by-step loads and 3×3 matrix distribution. The elastic modulus E representing the carbonate point mineral reaction area before erosion under each load is calculated using the above formula. n , hardness H n , rebound stiffness S n .
[0088] The samples that had been subjected to the nanoindentation test before erosion were then placed in a high temperature and high pressure immersion device and subjected to SCCO at 8 MPa and 40 °C for 5 days. 2 -Water immersion to quickly simulate erosion. After the experiment, the samples were taken out and allowed to air dry naturally.
[0089] In the divided carbonate point mineral reaction area, a second test area is selected using an optical or electron microscope provided in the nanoindentation tester, and a multiple load cycle loading nanoindentation experiment is performed in the second test area. The nanoindentation experiment setting conditions are the same before and after the erosion occurs.
[0090] According to the above formula, the elastic modulus E' under various loads after erosion of the carbonate point mineral reaction zone is calculated. n , hardness H' n , rebound stiffness S' n .
[0091] Fig.11 — Fig.12 The nanoindentation test curve of the white coal rock sample before and after erosion is shown.
[0092] Finally, the elastic modulus, hardness, and rebound stiffness obtained from the nanoindentation test before and after erosion under various loads in this area were compared, the erosion load was found, and the maximum indentation depth was calculated as the erosion depth through the erosion load.
[0093] Figure 13-Figure 15 A comparison chart of hardness, elastic modulus and rebound stiffness under different loads obtained before and after erosion of white coal rock samples is shown.
[0094] When the hardness H n With H n By comparing the hardness trends of the nanoindentation test before and after erosion, it can be found that when the load is 320mN, the hardness under each load after erosion reaches the maximum. Therefore, the erosion depth h under this load is calculated by the above formula. n =12.40μm; when according to the elastic modulus E n With E n By comparing the trend of the elastic modulus obtained by nanoindentation test before and after erosion, it can be found that the maximum value is reached when the load is 270mN. Therefore, the erosion depth h under this load is calculated by the above formula. n =10.62μm.
[0095] According to the rebound stiffness S n With S n 'When compared to the analysis, after erosion, F n Rebound stiffness under load S' n Equal to or close to F before erosion 1 When the stiffness under load is n =270mN, so the erosion depth h under this load is calculated by the above formula n =10.62μm;
[0096] Due to the change of the surface roughness of the sample after erosion, during the indentation process, the contact area A c The uncertainty in the calculation of leads to fluctuations in the calculated hardness and elastic modulus data. Therefore, there is a certain error in judging the maximum value of the hardness or elastic modulus under each load after erosion. However, the rebound stiffness S n The calculation only involves the initial stage of the rebound curve, thus avoiding the error caused by the contact area. In contrast, the results obtained using the stiffness analysis method are more consistent with the actual erosion depth.
Claims
1. A method for quantitatively characterizing the erosion degree of CO2 water-rock reaction based on indentation experiment, characterized in that: The following steps are involved: Step S1, grinding and polishing the rock sample until the surface roughness meets the test requirements of the nanoindentation experiment, and then pre-treating the rock sample, dividing the mineral reaction area on the surface of the rock sample according to the difficulty of the CO2 water-rock reaction; In step S1, the rock sample pretreatment process is to use SEM / EDS electron microscope to determine the heterogeneity of the rock sample; Step S2: Select a first test area in the mineral reaction area on the surface of the rock sample, and perform a matrix-type nanoindentation test with multiple load cycles, and calculate the elastic modulus E under each load before the erosion of the area based on the load-displacement curve obtained by the nanoindentation test. n , Hardness H n , rebound stiffness S n ; Step S3, treating the rock sample through a high temperature and high pressure immersion test device to quickly simulate the erosion phenomenon on the rock surface, and then naturally air-drying; Step S4: Select a second test area in the same mineral reaction area on the surface of the rock sample, and perform a matrix-type nanoindentation test with multiple load cycles under the same experimental conditions, and the first test area and the second test area do not affect each other, and calculate the elastic modulus E under each load after erosion of the area based on the load-displacement curve obtained by the nanoindentation test. n ', Hardness H n ', Rebound stiffness S n '; Step S5: The elastic modulus E obtained by two nanoindentation tests before and after the erosion n With E n ', Hardness H n With H n ', Rebound stiffness S n With S n 'Conduct comparative analysis, when load F n The rebound stiffness S n 'When the rebound stiffness S1 of the first test area under the initial load is closest, the load F n is the erosion load in the mineral reaction area; when the hardness H n ' or elastic modulus E n 'The corresponding load F when reaching the maximum n is the erosion load; finally, the maximum indentation depth is calculated by the erosion load as the erosion depth.
2. The method for quantitatively characterizing the erosion degree of CO2 water-rock reaction based on indentation experiment according to claim 1 is characterized in that: In step S1, the rock sample is a block rock sample, and the rock surface is finely polished step by step using sandpaper of various mesh sizes, and finally the rock surface is polished using an argon ion polishing device until the rock surface roughness meets the requirements of the nanoindentation experiment.
3. The method for quantitatively characterizing the erosion degree of CO2 water-rock reaction based on indentation experiment according to claim 1 is characterized in that: In step S2, the nanoindentation experiment setting conditions are 50mN, 100mN, 160mN, 210mN, 270mN, 320mN, 370mN, 430mN, and 480mN stepwise loads and 3×3 matrix layout.
4. The method for quantitatively characterizing the erosion degree of CO2 water-rock reaction based on indentation experiment according to claim 1 is characterized in that: In step S5, the elastic modulus E n With E n ', Hardness H n With H n ', Rebound stiffness S n With S n ' are respectively the average values of elastic modulus, hardness and rebound stiffness calculated at each indentation point in the matrix distribution in the first test area or the second test area under the same load.
5. The method for quantitatively characterizing the erosion degree of CO2 water-rock reaction based on indentation experiment according to claim 1 is characterized in that: In step S5, each indentation point in the matrix in the second test area is placed under the erosion load F n The maximum indentation depth h max The average value is calculated to obtain the erosion depth h n .
